2004
DOI: 10.1023/b:jarg.0000029492.54243.3c
|View full text |Cite
|
Sign up to set email alerts
|

Human Cervical Mucus Can Act in Vitro as a Selective Barrier Against Spermatozoa Carrying Fragmented Dna and Chromatin Structural Abnormalities

Abstract: Purpose : We have carried out experiments to determine if human cervical mucus can act as an in vitro selective barrier against spermatozoa morphologically normal that carry genetic structural abnormalities. Methods : Sperm chromatin abnormalities have been evaluated by Chromomycin A 3 and "endogenous" nick translation. Results : The data obtained have shown that spermatozoa possessing higher levels of DNA protamination are more proficient in crossing the cervical mucus barrier. Moreover, the levels of positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
(46 reference statements)
1
12
0
1
Order By: Relevance
“…Their results provided clear support for this hypothesis and showed that the epithelial cells were actively able to discriminate between spermatozoa carrying normal or unstable chromatin. These results are in accordance with an earlier study of human spermatozoa [40] showing that cervical mucus could act as a barrier against the progress of DNA-damaged cells, possibly because the DNA-damaged cells are less motile [41]. The importance of sperm-oviduct epithelial cell binding in controlling sperm quality has been reported in other in vitro studies [42][43][44][45][46][47] and has been proposed as a method for predicting fertility in cows [48] and pigs [49].…”
Section: Sperm Dna and Oviductal Interactionssupporting
confidence: 91%
“…Their results provided clear support for this hypothesis and showed that the epithelial cells were actively able to discriminate between spermatozoa carrying normal or unstable chromatin. These results are in accordance with an earlier study of human spermatozoa [40] showing that cervical mucus could act as a barrier against the progress of DNA-damaged cells, possibly because the DNA-damaged cells are less motile [41]. The importance of sperm-oviduct epithelial cell binding in controlling sperm quality has been reported in other in vitro studies [42][43][44][45][46][47] and has been proposed as a method for predicting fertility in cows [48] and pigs [49].…”
Section: Sperm Dna and Oviductal Interactionssupporting
confidence: 91%
“…Cryptic female choice, whereby females actively select more advantageous sperm, remains a very appealing albeit very poorly documented phenomenon (Eberhard, ). Evidence exists for selective processes by cervical mucus and the uterotubal junction (Bianchi et al, ; Watanabe et al, ); indeed, retention of sperm with compromised chromatin in the cervical mucus is probably the best example of cryptic female choice (Bianchi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa have previously been shown to be immotile in luteal phase mucus in vivo and in vitro, resulting in a failure to penetrate cervical mucus in vitro experiments. [10][11][12][13] Our results may indicate that this does not necessarily affect that passive transport of spermatozoa, which may not be blocked during the luteal phase. Similar numbers of motile spermatozoa are found within the oviduct during the luteal as in the early-to midfollicular phase of the cycle, as previously reported by studies that examined the presence of spermatozoa in different compartments of the genital tract after intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the highest number of spermatozoa can be detected in the fallopian tube during the preovulatory phase. [10][11][12][13][14] With regard to sperm transport, our interpretation of the results of HSS is based on the assumptions that the properties of the labeled material used for examination are similar to those of human spermatozoa and that there is no separation of label from the carrier in vivo. Various radiolabeled compounds have been used the past 30 years for radionuclide imaging of the female genital tract, including aggregates of human albumin, radioactive inert gases, and labeled spermatozoa.…”
Section: Discussionmentioning
confidence: 99%